1999
DOI: 10.1029/1998jd100012
|View full text |Cite
|
Sign up to set email alerts
|

A case study of gas‐to‐particle conversion in an eastern Canadian forest

Abstract: Abstract. Aerosol and trace gas measurements were made at Kejimkujik National Park, Nova Scotia, Canada, during the summer of 1996. A case study from July 7-8 provides evidence of nucleation and condensation of products related to the oxidation of different biogenic emissions. Particles from 5 nm to 50 nm in diameter evolved during the afternoon and early evening associated with variations in isoprene. Late in the evening the ix-and [5-pinene mixing ratios and the aerosol particle volume increased. Soon after,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
65
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(71 citation statements)
references
References 48 publications
5
65
1
Order By: Relevance
“…There are several reports for clean, mountain sites: 2.1 nm hr −1 , 1.6 nm hr −1 (Weber et al, 1997), and 3 to 4.5 nm hr −1 (Weingartner et al, 1999). Similar growth rates of 2 to 3 nm hr −1 have been reported for sites in the boreal forest (Mäkelä et al, 1997;Leaitch et al, 1999;Kulmala et al, 2001a), 2 to 5 nm hr −1 over the south Pacific (Weber et al, 1998), and 4.8 nm hr −1 for a rural area impacted by high SO 2 (Verheggen and Mozurkewich, 2002). Dramatically larger growth rates of 360 to 1200 nm hr −1 have been reported by O'Dowd et al (2002) for a site on the coast of Ireland.…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…There are several reports for clean, mountain sites: 2.1 nm hr −1 , 1.6 nm hr −1 (Weber et al, 1997), and 3 to 4.5 nm hr −1 (Weingartner et al, 1999). Similar growth rates of 2 to 3 nm hr −1 have been reported for sites in the boreal forest (Mäkelä et al, 1997;Leaitch et al, 1999;Kulmala et al, 2001a), 2 to 5 nm hr −1 over the south Pacific (Weber et al, 1998), and 4.8 nm hr −1 for a rural area impacted by high SO 2 (Verheggen and Mozurkewich, 2002). Dramatically larger growth rates of 360 to 1200 nm hr −1 have been reported by O'Dowd et al (2002) for a site on the coast of Ireland.…”
Section: Introductionsupporting
confidence: 53%
“…Most reported observations of nucleation have been in more remote locations. These have included coastal areas (O'Dowd et al, 2002;Weber et al, 1998), the marine boundary layer (Covert et al, 1992;Weber et al, 1995), the Arctic (O' Dowd et al, 1997;Wiedensohler et al, 1996), the free troposphere (Clarke, 1992;de Reus et al, 1998), the vicinity of clouds (Hegg et al, 1990;Clarke et al, 1999), remote continental areas (Weber et al, 1997;, over continental forests (Mäkelä et al, 1997;Leaitch et al, 1999;Kulmala et al, 2001b), in semi-rural areas Verheggen and Mozurkewich, 2002) and in urban areas (Woo et al, 2001;Stanier et al, 2004). Thus, it is clear that nucleation can occur in almost any environment, subject to a favorable set of conditions; these seems to include a suitable source of condensable vapor, high UV radiation intensity, low aerosol surface area, and high relative humidity although not all reports agree on the necessity of all these factors.…”
Section: Introductionmentioning
confidence: 99%
“…One could determine the CCN number concentration from a calibration constant applied to deltaV (e.g. Leaitch et al, 1999). Due to the limitations discussed above, it is unreasonable to expect to determine accurate CCN number concentrations using this approach to CCN measurements in the field where the chemical composition may change over time.…”
Section: Water Uptake: Cloud Condensation Nucleus Countermentioning
confidence: 99%
“…Bilde and Svenningsson, 2004;Cruz and Pandis, 1997;Hegg et al, 2001;Leaitch et al, 1999;Snider et al, 2003;Stroud et al, 2007). One could determine the CCN number concentration from a calibration constant applied to deltaV (e.g.…”
Section: Water Uptake: Cloud Condensation Nucleus Countermentioning
confidence: 99%
“…However, recent field studies have observed particle formation possibly related to iodine chemistry in the marine environment and references within) and volatile organic compounds (VOCs) in remote forested regions (Marti et al, Correspondence to: J. B. Burkholder (burk@al.noaa.gov) 1997; Kavouras et al, 1998Kavouras et al, , 1999Leaitch et al, 1999). The evaluation and impact of these sources of new particles is currently an active area of atmospheric research.…”
Section: Introductionmentioning
confidence: 99%